The Council of Europe Convention on Preventing and Combating Violence against Women and Domestic Violence in the Polish Social Safeguard System - Magdalena Tabernacka (Nordicum-Mediterraneum, 2017)
The ratification of the Council of Europe Convention on preventing and combating violence against women and domestic violence in Poland was preceded by a heated debate. From the very beginning it was be object of political battles between the conservative and liberal circles. Culturally and socially conditioned position of women has influenced its operation and the scope of its implementation. The Convention is a universally binding tool which guarantees the protection of human rights in events of violence against the woman and children. The case of this Convention in Poland proofs the existence of a universal European understanding of human rights protection standards. The Convention thus has a protective function not only for individuals but also, in a broader context, for the common European cultural identity.